Circulating levels of inflammation-associated miR-155 and endothelial-enriched miR-126 in patients with end-stage renal disease - Wang,Honglei (2012)
Circulating microRNAs (miRNAs) may represent a potential noninvasive molecular biomarker for various pathological conditions. Moreover, the detection of circulating miRNAs can provide important novel disease-related information. In particular, inflammation-associated miR-155 and endothelial-enriched miR-126 are reported to be associated with vascular homeostasis. Vascular damage is a common event described in end-stage renal disease (ESRD). We hypothesized that miR-155 and miR-126 may be detectable in the circulation and serve as potential biomarkers for risk stratification. In this study, we assessed miR-155 and miR-126 in the plasma of 30 ESRD patients and 20 healthy controls using real-time quantification RT-PCR. The circulating levels of miR-155 and miR-126 were significantly reduced in patients with ESRD compared to healthy controls. However, there was no significant difference of circulating miR-155 and miR-126 levels between prehemodialysis and posthemodialysis patients. Furthermore, both circulating miR-126 and miR-155 correlated positively with estimated glomerular filtration rate (miR-126: r = 0.383, P = 0.037; miR-155: r = 0.494, P = 0.006) and hemoglobin (miR-126: r = 0.515, P = 0.004; miR-155: r = 0.598, P < 0.001) and correlated inversely with phosphate level (miR-126: r = -0.675, P < 0.001; miR-155: r = -0.399, P = 0.029). Pearson’s correlation was used to compare circulating levels of miRNAs with clinical parameters. These results suggested that circulating miR-155 and miR-126 might be involved in the development of ESRD. Further studies are needed to demonstrate the role of circulating miR-155 and miR-126 as candidate biomarkers for risk estimation.